A Look at Plastic Bags and Alternatives (Journal of Geography, Meteorology and Environment, 2020)
Bags are essential items in the day to day activities of man, therefore, their continued use seem undeniably essential and unstoppable for many consumers. At present plastic bags have dominated the bag market against other alternatives. However, the dominant use of plastic bags have been queried as a result of its non-biodegradable nature and its environmental impact. This paper takes a cursory look at plastic bags and some available alternatives in order to highlight their impact on the environment throughout their life cycle. Plastic bags have alternatives in form of paper bags, tote bags, hemp bags, woollen bags, and degradable plastic bags. This paper is based on the concept of best practicable environmental option(s) (BPEO) and waste management hierarchy (WMH). BPEO advocates adopting the option that provides the most benefits and the least damageto the environment, as a whole, at acceptable cost, in the long term as well as the short term. While WMH promotes waste avoidance and reduction principle ahead of recycling and disposal principles. The review discovered that despite the myriad of proffered alternatives, none exist with zero impact on the environment. This paper recommends that all options be extensively juxtaposed from the process of resource extraction to the final waste disposal stage to determine best practicable environmental options. Waste management hierarchy which advocates reduction, reuse and recycling will be pivotal in reducing observed impacts from recommended bag type when employed in waste management planning.
Keywords: Plastic bags; paper bags; degradable bags; alternatives; waste management